1997
DOI: 10.1021/ja972292i
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation of Stilbene Derivatized Fatty Acids and Phospholipids in Monolayers and Vesicles1

Abstract: Synthetic fatty acid and phosphatidylcholine amphiphiles incorporating a trans-stilbene (TS) chromophore in the fatty acid chain have been found to exhibit sharp changes in absorption and fluorescence spectra upon self-assembly in Langmuir−Blodgett films and aqueous dispersions. The spectral changes are readily associated with aggregates in which there is a strong noncovalent interaction between the TS chromophores. In this paper, we report determination of the size, structure, and properties of these “supramo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(81 citation statements)
references
References 51 publications
8
73
0
Order By: Relevance
“…The authors who studied amphiphiles 11 and 12 suggested that the photoresponse of the azobenzene amphiphiles in the vesicles are strongly dependent on their aggregated state. [17,18] As counterparts of the self-assembly of azobenzene amphiphiles in aqueous conditions, self-assemblies of the azobenzenes 13…”
Section: Photocontrollable Self-assemblies Based On Strategy 2: Photomentioning
confidence: 99%
See 2 more Smart Citations
“…The authors who studied amphiphiles 11 and 12 suggested that the photoresponse of the azobenzene amphiphiles in the vesicles are strongly dependent on their aggregated state. [17,18] As counterparts of the self-assembly of azobenzene amphiphiles in aqueous conditions, self-assemblies of the azobenzenes 13…”
Section: Photocontrollable Self-assemblies Based On Strategy 2: Photomentioning
confidence: 99%
“…Thus, azobenzene-appended melamine 15 was prepared and its co-aggregation with 5,5'-diethylbarbituric acid (17) in CDCl 3 was investigated (Scheme 10). [22] For 15, steric crowding of the N-substituents increases with trans!cis isomerization in the aggregated state (Scheme 11).…”
Section: Photocontrollable Self-assemblies Based On Strategy 3: Photomentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 4, the PUC‐S1 film exhibits three characteristic absorption bands at 316, 328, and 338 nm, with the maximum peak occurring at 316 nm. Related to the maximum at 334 nm from the polymer solution, the redshift observed for the maximum at 338 nm in the UV spectrum of the polymer film could be tentatively associated with the predominance of stilbene aggregates, the size, structure, and properties of which were shown in other stilbene amphiphiles 28, 29. Subsequent irradiation of the polymer film indicated that the absorption spectra had curve profiles similar to those in solution, and the absorption bands decreased monotonously in favor of the formation of the cis species.…”
Section: Resultsmentioning
confidence: 80%
“…It can be seen that there is a blue shift (from 298 to 284 nm for Y21 and from 292 to 283 nm for Y34) in LB films deposited at high surface pressure compared with the films deposited at low surface pressure. Both theoretical [32] and experimental [33] reports in the literature suggest that small aggregates of from two to six p-conjugated molecules can alter the absorption and fluorescence spectra of the isolated chromophore, thus leading to blue-shifted absorption and red-shifted emission. In our case, the blue-shifted spectra for the film deposited at high surface pressure compared with the film deposited at low surface pressure are attributed to the formation of H aggregates, in which the long axes of the molecules are aligned in a general face-to-face arrangement.…”
Section: Transferred Films On a Solid Supportmentioning
confidence: 99%